The link between carbon emissions, agricultural output and industrial output: evidence from South Africa - Sibanda, Mabutho; Ndlela, Hlengiwe (Journal of Business Economics and Management, 2020)
This study seeks to establish the relationship between carbon emissions, agricultural output and industrial output in South Africa. It uses data from 1960 to 2017 based on an annual frequency, giving a total of 58 annual observations. The Autoregressive Distributed Lag technique is employed to estimate the model on a bivariate basis. The evidence shows that carbon emissions are not influenced by agricultural and industrial output. Conversely, agricultural output is influenced by carbon emissions and industrial output. The results suggest that climate change resulting from carbon emissions has led to reduced agricultural output, adversely affecting food security. The significant relationship between industrial and agricultural output suggests that a properly functioning industrial sector will cause an increase in the agricultural output. The study’s findings have implications for climate change and manufacturing policies in South Africa.